Tales from out there : the Barkley Marathons, the world's toughest trail race - Furtaw, Edwin (Pagosa Springs, CO : Ed Furtaw, 2010)
The Barkley Marathons is a 100 Mile Run and a 60 Mile Fun Run held annually in Frozen Head State Park near Wartburg, Tennessee in late March or early April. Since the race began in 1986, only 9 runners out of about 700 have finished within the 60-hour cutoff. The course itself, which has changed distance, route, and elevation many times since its inaugural run in 1986, currently consists of a 20-mile (32 km) loop with no aid stations except water at two points along the route and the runner's parked car at the beginning of the loop. Runners of the 100 Mile version run this loop five times, with loops three and four being run in the opposite direction and loop five being runner's choice. Runners of the 60 Mile Fun Run (considered to be harder than Hardrock) complete three circuits of the loop. With 54,200 feet (16,500 m) of accumulated vertical climb, the 100 Mile Run is considered to be one of the more challenging ultramarathons held in the United States, if not the world. In addition to running, competitors must find between nine and 11 books (varies per year) and remove a page from each book as proof of completion.
Includes bibliographical references.
Keywords: Furtaw, Edwin; Barkley Marathons (Tenn.).; Marathon running -- Tennessee; Running races -- Tennessee; Endurance sports -- Tennessee